2005
DOI: 10.1063/1.1947909
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and carrier dynamics in CdSe self-assembled quantum dots embedded in ZnxCdyMg1−x−ySe

Abstract: Articles you may be interested inEffect of metal oxide morphology on electron injection from CdSe quantum dots to ZnO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The rise time is determined by fitting the rising process with the Boltzmann sigmoidal function where B 1 is the initial value, B 2 is the final value, t s indicates the time center, and τ R represents the time constant for the rising process. The rise time (τ R ) for FX obtained from the fitting is 101 ± 5 ps (results shown in Figure a), which value is larger than that in CdSe QDs (20–40 ps). , The decay curve of the QD samples can be well-fitted by a double-exponential function where I b represents the noise. The fitting results are plotted as solid lines in Figure a.…”
Section: Results and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The rise time is determined by fitting the rising process with the Boltzmann sigmoidal function where B 1 is the initial value, B 2 is the final value, t s indicates the time center, and τ R represents the time constant for the rising process. The rise time (τ R ) for FX obtained from the fitting is 101 ± 5 ps (results shown in Figure a), which value is larger than that in CdSe QDs (20–40 ps). , The decay curve of the QD samples can be well-fitted by a double-exponential function where I b represents the noise. The fitting results are plotted as solid lines in Figure a.…”
Section: Results and Discussionmentioning
confidence: 87%
“…The rise time (τ R ) for FX obtained from the fitting is 101 ± 5 ps (results shown in Figure 4a), 39 which value is larger than that in CdSe QDs (20−40 ps). 40,41 The decay curve of the QD samples can be well-fitted by a double-exponential function 38…”
Section: E E Ementioning
confidence: 99%
“…The CdSe SAQDs have very high ionization energy due to the larger size; and its crystal lattice is coherently connected to the host ZnSe matrix (high quality dislocation-free interface). The results of carrier dynamics in CdSe SAQDs from [17] suggest that the recombination processes are inherently faster in smaller QDs. In fact, we observed that the high-energy part of the NCs PL peak has a faster relaxation than the low-energy part (the smaller the NC size, the higher the energy of the PL emission), as is clearly shown in figure 6(a).…”
Section: Optical Characterizationsmentioning
confidence: 99%
“…The experiment was carried out with a cw-He-Cd laser at a 325 nm excitation wavelength and at 2 mW power. The typical spectra of the photoluminescence of CdSe/ZnCdMgSe QDs are presented in [2,8]. The emission peak of the PL was centred at 585 nm at room temperature, and its full width at half-maximum (FWHM) was about 8 nm for the sample used.…”
Section: Cw Low Power Excitationmentioning
confidence: 99%